PROSPECTS AND DOMINANTS OF ORGANIZATIONAL CAPITAL MANAGEMENT OF THE ENTERPRISE ON THE BASIS OF MODERN ERP SYSTEMS - AZAROVA, Anzhelika; VENZHYK, Olha; KRAIEVSKA, Аlla; YURCHUK, Natalya; MIRONOVA, Yuliia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the basic concepts of formation of definition of organizational capital, which allowed to substantiate its own concept for its further research. A system of evaluative criteria for comparing different latest intellectual information systems has been formed. On the basis of the built set of criteria, the disadvantages and advantages of modern ERP systems in the aspect of management on the basis of organizational capital of the enterprise are analyzed and the choice of optimal among them to solve the tasks of research is substantiated.The analysis of ERP systems showed their key role in the development of targeted organizational capital management, identifying the main prospects and challenges. It has been proven that the integration of modern ERPs contributes to the automation of processes, improving the efficiency of resource management and strategic development of companies. The dominants of their development are flexibility, scalability, integration with innovative technologies and data safety. Therefore the use of optimal intellectual information solutions such as IS "VPRAVNO" allows businesses to quickly adapt to changes and increase competitiveness in the conditions of building relationships in a digital ecosystem. At the same time "VPRAVNO"  not only simplifies management processes, but also helps companies to effectively develop intellectual capital and properly manage intangible assets. Thanks to its flexible software modules and powerful hardware this system facilitates the protection and management of intellectual property, including patents, trademarks and other rights that are of particular importance in today's competitive environment. Combined with innovative automation tools "VPRAVNO" enables companies to quickly scale their business, form and maintain the necessary relationships with partners and customers, and protect and develop their unique developments. As a result the implementation of such a solution allows companies to create stable competitive advantages and strengthen their market positions by forming an effective interaction between managerial, technological and intellectual resources.
Keywords: organizational capital; definition; concepts; object of sale; comparison criteria; intellectual information systems